1954
DOI: 10.1103/physrev.93.199
|View full text |Cite
|
Sign up to set email alerts
|

Cross Sections for Production ofIn115mandAu19

Abstract: Cross sections for the reactions In 115 (w,w')In 115m and Au l97 (n,n , )A\x l91m have been measured from the reaction thresholds to 5.5 Mev. The lowest mean energy for which the In 115w excitation was observed was 440 kev with an energy spread of ±100 kev; the cross section rises to a peak value of 0.36 barn at 2.5 Mev. The lowest mean energy for which the Au 197w excitation was observed was 420 kev with an energy spread of ±40 kev; the cross section rises to a peak value of 1.3 barns at 2.5 Mev. Both cross s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1957
1957
1968
1968

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 41 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…A reanalysis of the decay data has indicated that there is no definitely observable 23.9-min component in the decay of the counts in the interval between 39 and 80 keV. Any such component affects the Ho 165 Figure 6 shows the present results of the activation cross section for the In 115 (n,^')I nll5wreac tion compared with the results of Ebel and Goodman, 29 Grench and Menlove, 30 Cohen, 31 Martin et at., 32 (n,2n) reaction, which has a threshold of 9.1 MeV. Figure 7 shows the present cross-section measurements for the Al 27 (w,o:)Na 24 reaction compared with the curve from Ref.…”
Section: Comparisons With Other Experimental Resultsmentioning
confidence: 95%
“…A reanalysis of the decay data has indicated that there is no definitely observable 23.9-min component in the decay of the counts in the interval between 39 and 80 keV. Any such component affects the Ho 165 Figure 6 shows the present results of the activation cross section for the In 115 (n,^')I nll5wreac tion compared with the results of Ebel and Goodman, 29 Grench and Menlove, 30 Cohen, 31 Martin et at., 32 (n,2n) reaction, which has a threshold of 9.1 MeV. Figure 7 shows the present cross-section measurements for the Al 27 (w,o:)Na 24 reaction compared with the curve from Ref.…”
Section: Comparisons With Other Experimental Resultsmentioning
confidence: 95%